One who loves knowledge : studies in honor of Richard Jasnow - Bryan, Betsy Morrell; Smith, M. (Mark), 1951-; Di Cerbo, Christina; Escolano Poveda, Marina; Waller, Jill S.; Jasnow, Richard (Material and visual culture of ancient Egypt ;, 2022)
"The thirty-nine articles in this volume, One Who Loves Knowledge, have been contributed by colleagues, students, friends, and family in honor of Richard Jasnow, professor of Egyptology at Johns Hopkins University. Despite his claiming to be "just a demoticist," Richard Jasnow's research interests and specialties are broad, spanning religious and historical topics, along with new editions of demotic texts, including most particularly the Book of Thoth. A number of the authors demonstrate their appreciation for Jasnow's contributions to the understanding of this difficult text. The volume also includes other studies on literature, Ptolemaic history, and even the god Thoth himself, and features detailed images and abundant hieroglyphic, hieratic, demotic, Coptic, and Greek texts"--